Returning to Judgment Bernard Stiegler and Continental Political Theory. - Turner, Ben. (Bielefeld : State University of New York Press, 2023)
Explores the importance of political judgment in the work of Bernard Stiegler, and argues his approach to judgment marks an important break with continental political thought.
Historical Judgments and the Totalization of the Political -- Conclusion: The Many Origins of the Political -- Conclusion: A Pharmacology of the Political -- Notes -- Bibliography -- Index
Description based upon print version of record.
JSTOR
Keywords: Ontology -- Political aspects; Political science -- Philosophy; Philosophy : Continental Philosophy; Philosophy : Critical Theory; Philosophy : Post Structuralism; Politics and Law : Political Theory; Sociology : Social Theory; Ontologie -- Aspect politique; POLITICAL SCIENCE / History & Theory